2020
DOI: 10.1002/ijfe.2067
|View full text |Cite
|
Sign up to set email alerts
|

The profitability of Ichimoku Kinkohyo based trading rules in stock markets and FX markets

Abstract: This paper examines the profitability of trading rules based on a Japanese technical analysis method called Ichimoku Kinkohyo. First, the trading strategies based on several entry and exit strategies of Ichimoku Kinkohyo charting were designed. Then, we investigated their profitability on four stock indices of the world's famous stock exchanges over 1995 to 2018, and on four important currency pairs over 2003 to 2018. By using the default parameter setting (9, 26, 52) of Ichimoku Kinkohyo, we found that althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…Note that, in almost all of the trading rules based on candlestick charts another parameter denoting the current market trend is used. In this work, the market trend is detected using equation (2) in which the µ w denotes the w day moving average which is computed by equation (3), and v is a window size for the number of candles before time t to be considered in the calculation of the trend.…”
Section: Trading Rules Based On Candlestick Chart Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that, in almost all of the trading rules based on candlestick charts another parameter denoting the current market trend is used. In this work, the market trend is detected using equation (2) in which the µ w denotes the w day moving average which is computed by equation (3), and v is a window size for the number of candles before time t to be considered in the calculation of the trend.…”
Section: Trading Rules Based On Candlestick Chart Patternsmentioning
confidence: 99%
“…In (A.1) ψ t (P t ) shows the trading signal at time step t. This function is used in SignalingF unction of (A.8). In (A.1), MT is defined in (2).…”
Section: Appendix a Rules By The Traditional Rule-based Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past two decades, the effect of the Ichimokubased strategies on different market environments has been studied in many works. Deng et al [9] investigated the profitability of Ichimoku-based trading rules. They indicated that some Ichimoku-based trading strategies could prove profitable when trading stock indices, but not when trading currencies.…”
Section: Introductionmentioning
confidence: 99%
“…The technical analysis method generally assumes that history will repeat [8]- [10], and the market can be predicted by judging the change of price movement through one or more technical indicators [11]. For stock prices or futures prices' fluctuation analysis, time series analysis method is one kind of the most commonly used approaches to predict their future prices.…”
Section: Introductionmentioning
confidence: 99%